Facial recognition technology with reducing the risk of spreading the COVID-19 / Muhammad Arif Azhad Amalulkhair ... [et al.] - Amalulkhair, Muhammad Arif; Mahadi, Nur Akmal; Abdullah, Nur Adlina; Sattaratpaijit, Kannaphat (2022)
Project management, which originated in the mid-20th century, has evolved into a distinct way of managing business activities today. Another significant development is the widespread acceptance of the importance of innovation and technology in organizational change, growth, and profitability. It is unsurprising that innovation development is frequently carried out as a project. However, both project management and innovation studies have emerged as independent fields over time. In this work, we attempt to define innovation project management and to define the distinctive nature of innovation projects against traditional projects. We contribute to the budding academic discourse on the interaction between innovation and project management by doing so.